2017
DOI: 10.1016/j.rasd.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

School refusal behaviour: Are children and adolescents with autism spectrum disorder at a higher risk?

Abstract: Individual characteristics of students with autism spectrum disorders and school refusal behavior. Autism, 1362361317748619.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 110 publications
(257 reference statements)
8
57
0
Order By: Relevance
“…Of particular relevance to this study are the risks of non-attendance at school and subsequent disengagement from formal learning. Although the extent of non-attendance amongst this group of students has not been identified, disability is identified as a risk factor for absenteeism (Kearney, 2008) and Munkhaugen, Gjevik, Pripp, Sponheim, and Diseth (2017) identify that school refusal behaviour is significantly higher in children and adolescents with ASD than in typically-developing students. Archer, Filmer-Sankey, and Fletcher-Campbell (2003, p. v) investigated causes of school phobia and school refusal, defining school phobia as 'acute anxiety about attending school, students who cannot face school'.…”
Section: Asd and Anxietymentioning
confidence: 99%
“…Of particular relevance to this study are the risks of non-attendance at school and subsequent disengagement from formal learning. Although the extent of non-attendance amongst this group of students has not been identified, disability is identified as a risk factor for absenteeism (Kearney, 2008) and Munkhaugen, Gjevik, Pripp, Sponheim, and Diseth (2017) identify that school refusal behaviour is significantly higher in children and adolescents with ASD than in typically-developing students. Archer, Filmer-Sankey, and Fletcher-Campbell (2003, p. v) investigated causes of school phobia and school refusal, defining school phobia as 'acute anxiety about attending school, students who cannot face school'.…”
Section: Asd and Anxietymentioning
confidence: 99%
“…Peers believed bullying was a problem but wanted to help those who were bullied (Dillenburger et al 2017). Munkhaugen et al (2017) reported that refusal to attend school among pupils with ASD has only been studied to a limited extent, but is considered a serious problem. The results revealed that school refusal was significantly higher among pupils with ASD compared with typically developing pupils (Munkhaugen et al 2017).…”
Section: Mainstream School and Special Solutions For Pupils With Asdmentioning
confidence: 99%
“…Students with ASD are also at risk of school refusal behavior. A Norwegian study showed that school refusal behavior was significantly higher in students with ASD, aged 9 to 16 years without ID, as compared to typically developing students (TD-students; Munkhaugen et al 2017). The researchers also suggest that students with normal range IQ and ASD are more at risk of school refusal behavior than students with ID and ASD.…”
Section: Introductionmentioning
confidence: 99%